(untitled) (The International Journal of Educational Sciences and Arts, 2025)
Exile is a prominent feature of the contemporary Arab novel and has maintained a consistent presence in the Iraqi novel over the past three decades. However, the issue of exile has occupied a central place in the novels of expatriate Iraqi writer Inaam Kachachi. In "The Nabiza," the author offers a different dimension in addressing this theme. She transcends the traditional view of exile as a state of alienation reduced to a place of loss, depicting it as an existential and cultural space for reshaping the self, which is recovered through the narrative of suffering and longing, and rebuilt through reconciliation with contradictions. This makes the novel a contemplative text that does not rely on the tragedies of exile, but rather goes beyond that to ask pivotal questions about belonging and existence. Thus, the study concludes that "The Nabiza" offers a comprehensive human vision of exile, making it deeper than just an ordeal, but rather a journey in search of the meaning of life, in which the exile seeks to rebuild himself amidst the fragmentation of place and memory. Hence, this study seeks to analyze the manifestations of his presence in the novel through the tension of identity through cultural paradoxes and bilingualism, memory as a tool of resistance and an archive of fragility and pain, and the possibilities of rebuilding the self in the space of exile.